2020
DOI: 10.1007/s12671-019-01298-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of mindfulness and self-compassion in depressive symptoms and affect: A Comparison between Cancer Patients and Healthy Controls

Abstract: Objectives Mindfulness and self-compassion are related to psychological well-being and can be regarded as personal resources. It is, however, unclear whether these resources are always beneficial (direct effect) or only in stressful circumstances (buffer effect). We therefore examined whether mindfulness and self-compassion are equally or more strongly related to depressive symptoms and affect in cancer patients, compared to healthy controls. Methods Using a case-control design, 245 cancer patients were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
8
1
1
Order By: Relevance
“…7,9 In the context of cancer, cross-sectional research has found that higher self-compassion is related to better psychological well-being in people with prostate cancer, 10 breast cancer, 11 lung cancer, 12 and heterogeneous cancer types. 13 A longitudinal study in Chinese cancer patients found that higher self-compassion at the time of cancer diagnosis predicted lower depression, anxiety, and fatigue during medical treatment. 14 Currently, there are conflicting findings and opposing views on the conceptualisation of self-compassion.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 In the context of cancer, cross-sectional research has found that higher self-compassion is related to better psychological well-being in people with prostate cancer, 10 breast cancer, 11 lung cancer, 12 and heterogeneous cancer types. 13 A longitudinal study in Chinese cancer patients found that higher self-compassion at the time of cancer diagnosis predicted lower depression, anxiety, and fatigue during medical treatment. 14 Currently, there are conflicting findings and opposing views on the conceptualisation of self-compassion.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study showed that EFT can significantly reduce depression and increase self-compassion in patients with breast cancer. 8 Self-critical 9 Self-frightener 10 Self-interruption 11 Systematic evocative unfolding 12 Problematic reactions 13 Vulnerability 14 Meaning protest 15…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In the context of cancer, some cross-sectional studies have confirmed that higher self-compassion is closely associated with fewer psychological symptoms (i.e., depression, anxiety, and stress) in patients with breast cancer, 13 prostate cancer, 14 and heterogeneous cancer types. 15 A longitudinal study with heterogeneous Chinese cancer patients found that higher self-compassion at first cancer diagnosis predicted lower depression, anxiety, and fatigue during medical treatment. 16 These studies suggest that self-compassion could be considered as a protective factor for cancer patients, providing kindness and warmth to patients in the face of suffering and improving psychological well-being.…”
mentioning
confidence: 99%